A Comparison of Different Methods for Rna and Dna Extraction From Formalin – Fixed Paraffin-Embedded Tissues From Different Cancer Samples - Kandalla, Nuha J.; Sabbah, Majeed A.; Khoshaba, Ramina M.; Abdulsalam, Diaa (Science Journal of University of Zakho, 2014)
RNA and DNA extracted from formalin-fixed paraffin-embedded (FFPE) tissue is problematic due to chemical modifications and continued degradation over time. we compared quantity of RNA extracted by two different protocols from 14 recently archived from patients suffered from different cancers distributed among formalin-fixed paraffin-embedded (FFPE) breast cancer tissues ,thyroid cancer tissues and Cervical uterus carcinoma tissues by using Guanidine isothiocyanate (GTC)with phenol-chloroform (protocol-1) and Silica Gel Column(SGC) dependent on spin column purification-based ( protocol- 2), to assess, which technique is the most efficient and reproducible in terms of total yield and purity. The results showed RNA isolated with SGC technique was characterized by higher mean concentration in a range (80-180) µg/ml ,but it give positive results to 12 sample with degradation in comparison with RNA isolated by the (GTC) technique (protocol-1), comparison with total RNA extraction from human blood ( two distinguished bands ) .In this study comparative methods have been performed to analyze the efficiency for extraction and purification of Genomic DNA from six selective FFPE Tissues samples, revealing that the extraction of DNA by using extraction modified method give good result with yield higher mean concentration of DNA in a range (160-260) µg/ml.The lysis of FFPE Tissues was enhanced by increased the concentration of proteinase K to30 mgfor 2 hour at 65C, which considered the best time for lysis tissues and heated comparable with results that obtained from lysis tissues by using 20mgfor (24 -48 hours) at 55C